Deficiency of fibroblast growth factor 2 (FGF‐2) leads to abnormal spermatogenesis and altered sperm physiology. Issue 12 (27th July 2018) - Saucedo, Lucía; Rumpel, Regina; Sobarzo, Cristian; Schreiner, Dietmar; Brandes, Gudrun; Lustig, Livia; Vazquez‐Levin, Mónica Hebe; Grothe, Claudia; Marín‐Briggiler, Clara
Abstract : In previous studies, we described the presence of fibroblast growth factor 2 (FGF‐2) and its receptors (FGFRs) in human testis and sperm, which are involved in spermatogenesis and in motility regulation. The aim of the present study was to analyze the role of FGF‐2 in the maintenance of sperm physiology using FGF‐2 knockout (KO) mice. Our results showed that in wild‐type (WT) animals, FGF‐2 is expressed in germ cells of the seminiferous epithelium, in epithelial cells of the epididymis, and in the flagellum and acrosomal region of epididymal sperm. In the FGF‐2 KO mice, we found alterations in spermatogenesis kinetics, higher numbers of spermatids per testis, and enhanced daily sperm production compared with the WT males. No difference in the percentage of sperm motility was detected, but a significant increase in sperm concentration and in sperm head abnormalities was observed in FGF‐2 KO animals. Sperm from KO mice depicted reduced phosphorylation on tyrosine residues (a phenomenon that was associated with sperm capacitation) and increased acrosomal loss after incubation under capacitating conditions. However, the FGF‐2 KO males displayed no apparent fertility defects, since their mating with WT females showed no differences in the time to delivery, litter size, and pup weight in comparison with WT males. Overall, our findings suggest that FGF‐2 exerts a role in mammalian spermatogenesis and that the lack of FGF‐2 leads to dysregulated sperm production and altered sperm morphology and function. FGF‐2‐deficient mice constitute a model for the study of the complex mechanisms underlying mammalian spermatogenesis. Abstract : Our findings showed that in wild type (WT) animals, FGF‐2 is expressed in germ cells of the seminiferous epithelium, in epithelial cells of the epididymis, and in the flagellum and acrosomal region of epididymal sperm. In the FGF‐2 knockout (KO) mice, we found alterations in spermatogenesis kinetics and enhanced daily sperm production compared to the WT males. A significant increase in sperm concentration and in sperm head abnormalities, as well as alterations in other sperm parameters (reduced tyrosine phosphorylation and increased acrosomal loss) were observed in FGF‐2 KO animals. Overall, the results suggest that FGF‐2 exerts a role in mammalian spermatogenesis, and that the lack of FGF‐2 leads to dysregulated sperm production and altered sperm morphology and function.